USING PICTURE MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES IN ENGLISH STUDY IN CLASS X OF MA. MIFTAHUL MIDAD LUMAJANG - Dyah Mahmawati (PPPM STIT MIFTAHUL MIDAD, 2022)
The problems in this research are: Can image media use in English study improve the learning outcomes of tenth-grade students at MA. Miftahul Midad Lumajang? Image media is a form of communication used to present information. The problem to be solved in this research is the low learning outcomes of tenth-grade students at MA. Miftahul Midad Lumajang. The method uses qualitative data and quantitative data. Data was obtained through teacher and student observation sheets. The results of the researcher's observations in the first cycle of the first meeting acquired an average value of 53.57%. The second meeting increased to 68.75 %. While in the second cycle, the first and second meetings increased by 75.00% and 87.50%. Therefore, the overall value of student activity was in a suitable category. The results of observing teacher activities in the first cycle of the first meeting and the second meeting, respectively, were 53, 57%, and 64.69%. In contrast, in the second cycle, the first meeting and second meeting increased to 71.43% and 89.89%, according to the indicator that the level of success of teacher activities was in a Good category. Student learning outcomes obtained after applying image media in English study were classical completeness in the first cycle, 20.08% increased to 95.80% in the second cycle, and classical absorption obtained in the first cycle was 54.58% to 75.42%. From these results, we can conclude that image media can improve student learning outcomes in MA. Miftahul Midad Lumajang.